Outdoor activities foster local plant knowledge in Karelia, NE Europe - Mattalia, G.; Svanberg, I.; Ståhlberg, S.; Kuznetsova, N.; Prūse, B.; Kolosova, V.; Aziz, M. A.; Kalle, R.; Soukand, R. (Scientific Reports, 2023)
Wild edible plants, particularly berries, are relevant nutritional elements in the Nordic countries. In contrast to decreasing global trends, approximately 60% of the Finnish population is actively involved in (berry) foraging. We conducted 67 interviews with Finns and Karelians living in Finnish Karelia to: (a) detect the use of wild edible plants, (b) compare those results with the published data about neighbouring Russian Karelians, and (c) document the sources of local plant knowledge. The results revealed three main findings. First, we observed a similarity in wild food plant knowledge among Karelians and Finns from Karelia. Second, we detected divergences in wild food plant knowledge among Karelians living on both sides of the Finnish-Russian border. Third, the sources of local plant knowledge include vertical transmission, acquisition through literary sources, acquisition from "green" nature shops promoting healthy lifestyles, childhood foraging activities performed during the famine period following WWII, and outdoor recreational activities. We argue that the last two types of activities in particular may have influenced knowledge and connectedness with the surrounding environment and its resources at a stage of life that is crucial for shaping adult environmental behaviours. Future research should address the role of outdoor activities in maintaining (and possibly enhancing) local ecological knowledge in the Nordic countries.